PENERAPAN PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIID MTs PONDOK PESANTREN DAARUN NAHDHA THAWALIB BANGKINANG - Arifatul hilma; Armis '; Nahor Murani Hutapea (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this research is low of mathematics learning outcomes of class VIIId of MTs PPDNTB in first semester of the academic year 2015/2016, with the aim to improve the learning process and improve learning result in mathematics in grade VIIId of MTs PPDNTB by implementation of cooperative structural with Numbered Head Togethr (NHT) approach. The subject of research were the students in the class VIIId of MTs PPDNTB that consist of 10 boys and 15 girls at the second semester of academic year 2015/2016. This research consist of two cycles that each cycle composed of 4 stages, such as planning, implementation, observation and reflection. At every end of a cycle, researcher doing out daily test. The research instrument consists of learning devices that involve Syllabus, Lesson Plan and Student Worksheet, and instrument data collector that involve the observation sheet and math achievement test. Observation sheets is analyzed by narrative descriptive analysis and math achievement test analyzed by quantitative descriptive. Based on the results of the research, show that the learning process has improved and the student’s mathematic learning outcomes also increased after applying cooperative learning with Numbered Head Together (NHT) structural approach. The number of students who reached the Minimum Mastery Criteria before the action is 36%, and increased at the first cycle 52% and also increased at the second cycle 76%.